The mediating role of spiritual orientation and subjective vitality in university students - YAMAN, NESLİHAN (My University, 2020)
This study aims to examine the mediating role of spiritual orientation and subjective vitality in the relationship between thriving and life satisfaction among university students. Data were sourced from a total of 527 participants: 428 females (81.2%) and 99 males (18.8%), from Istanbul Medeniyet University. The mean age of the participants was 20 (SD = 2.35). The Thriving Scale, Satisfaction with Life Scale, Spiritual Orientation Scale and Subjective Vitality Scale were utilized. Analyses were performed with the Structural Equation Model and The Pearson Product Moment Correlation, Path Analysis and Bootstrapping Test were used. According the road analysis result, the direct effect of spiritual orientation and subjective vitality in life satisfaction proved to be significantly high. The fit values of the model are within acceptable limits (χ²/SD = 0.00; p < 0.01; GFI = 0.99; CFI = 0.1; NFI = 0.99; RMSEA = 0.00). In the established model, 22% of the total variance of the life satisfaction variable is explained. The results of the bootstrapping process in the model prove to be significant (bootstrap coefficient model = 0.054, 95% G.A. = 0.022, 0.118). The findings were discussed in line with relevant literature and recommendations on their possible application have been given. Keywords: Life satisfaction, mediation, spiritual orientation, subjective vitality, thriving